Hippocampal Sclerosis - Ristic, Aleksandar; Raicevic, Savo; Bascarevic, Vladimir; Vojvodic, Nikola; Sokic, Dragoslav (Medical Research, 2023)
Hippocampal sclerosis is one of the most common causes of focal epilepsy. At the same time, hippocampal sclerosis is the most common surgical substrate in focal pharmacoresistant epilepsies. The hippocampus has a specific anatomical structure consisting of a total of four sectors. In a physiological context, the hippocampus is essential in many neuropsychological processes, so hippocampal sclerosis (an entity recognized and associated with epilepsy as early as the 19th century) is very interesting in terms of research. The pathohistological pattern of hippocampal sclerosis is now very precisely represented, which helps uniform recognition. The causes of hippocampal sclerosis are not known, but so far, numerous factors have been identified that are associated with the occurrence of this pathological process. There is no doubt that excitotoxicity, along with changes in the redox system, is the most essential pathophysiological mechanism. Hippocampal sclerosis is clinically very recognizable. Epilepsy patients whose basis is hippocampal sclerosis have very typical epileptic seizures consisting of an epigastric aura followed by a focal epileptic seizure characterized by confusion of consciousness and oroalimentary automatisms. Today, thanks to modern neuroimaging (primarily magnetic resonance imaging), the detection of this pathological pattern is exact and unambiguous.